2016
DOI: 10.1177/0962280216666564
|View full text |Cite
|
Sign up to set email alerts
|

Multiple imputation by chained equations for systematically and sporadically missing multilevel data

Abstract: In multilevel settings such as individual participant data meta-analysis, a variable is 'systematically missing' if it is wholly missing in some clusters and 'sporadically missing' if it is partly missing in some clusters. Previously proposed methods to impute incomplete multilevel data handle either systematically or sporadically missing data, but frequently both patterns are observed. We describe a new multiple imputation by chained equations (MICE) algorithm for multilevel data with arbitrary patterns of sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
134
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(140 citation statements)
references
References 42 publications
1
134
0
Order By: Relevance
“…() who showed that JM‐FJ and JM‐MLMM produce biased estimation of the variance components while the FCS‐LMM‐het approach provided consistent estimates in the context of clustered data. Some of our theoretical results extend the results obtained by Resche‐Rigon and White () who considered an LMM with only a random intercept.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…() who showed that JM‐FJ and JM‐MLMM produce biased estimation of the variance components while the FCS‐LMM‐het approach provided consistent estimates in the context of clustered data. Some of our theoretical results extend the results obtained by Resche‐Rigon and White () who considered an LMM with only a random intercept.…”
Section: Discussionsupporting
confidence: 88%
“…The jomo implementations for JM-MLMM-LN and JM-SMC allow a random covariance matrix and hence are denoted as JM-MLMM-LN-het and JM-SMC-het. Similar efforts have been made to extend both the FCS-LMM and FCS-LMM-het methods to impute categorical data using either generalized LMM (GLMM)-based MI methods (Resche-Rigon & White, 2016;Zhao & Yucel, 2009) or LN variables (FCS-LMM-LN and FCS-LMM-LN-het) (Enders, Keller, & Levy, 2017).…”
mentioning
confidence: 99%
“…Alternatively, researchers can conceptualize this as a missing data problem, with some covariates partially or completely missing at some data-contributing sites, and use methods like multiple imputation by chained equations that appropriately account for between-site heterogeneity to handle the missing data. 68,69 Whenever possible, researchers should specify their primary analysis and perform sensitivity analyses to examine the robustness of their results.…”
Section: Database-specific Confounder Lists Vs Common Confounder Lismentioning
confidence: 99%
“…Resulting from the extensive simulation studies, the proposed imputation approach also has good statistical properties in terms of bias and coverage rates. Moreover, our method, as opposed to recently proposed one‐stage imputation approach by Resche‐Rigon & White (), no longer requires (typically unreliable) estimates of standard errors around between‐study covariance parameters. Finally, it is freely accessible and is already implemented in the R package MICE (Van Buuren & Groothuis‐Oudshoorn, ).…”
Section: Discussionmentioning
confidence: 99%
“…Van Buuren () applied a Markov chain Monte Carlo (MCMC) method to draw θk. Resche‐Rigon & White () made a draw of θk using their large sample normal approximation (by applying the Fisher's transformation to the variance component). We, in the subsequent section, propose an (approximate) Bayesian approach to achieve step 2.…”
Section: Hierarchical MI Using Micementioning
confidence: 99%